METODE DISKUSI TERBIMBING DALAM MENINGKATKAN KOMPETENSI BERFIKIR KREATIF PADA PEMBELAJARAN IPAS - Laute, Varissa; Pomalingo, Samsi; Sarlin, Muhammad (SINERGI : Jurnal Riset Ilmiah, 2025)
This study is "Can the Use of Guided Discussion Methods Improve Students' Creative Thinking Competencies in Science Learning in Grade IV of SDN 4 Kopandakan?". The results of the study showed that students' learning outcomes in creative thinking in cycle I showed that out of 13 students who could achieve the KKM score were 9 students or 69%, while students who had not achieved the KKM score were 4 students or 31%. Furthermore, in cycle II there was an increase from 13 students who achieved the KKM score to 11 students or 85%, while 2 students or 15% did not achieve the KKM score. Thus, it can be concluded that through the guided discussion method assisted by Interactive Powerpoint media, it can improve students' learning outcomes in creative thinking in science learning in grade IV of SDN 4 Kopandakan.